Structural Characterization of Cistanche deserticola Polysaccharides and Its Protective Effect on High Glucose-Induced HK-2 Cell Injury - LUO Xinjie, LIU Jiangyun, YANG Jianhua, HU Junping (Shipin Kexue, 2025)
Objective: To investigate the structures of Cistanche deserticola polysaccharides (CDPs) and to evaluate the protective effect thereof on human renal proximal tubular epithelial (HK-2) cell injury and the underlying mechanism. Methods: The chemical composition, molecular mass, monosaccharide composition and possible structure of CDPs were detected using the sulfuric acid phenol method, the hydroxyl biphenyl method, the Coomassie brilliant blue method, ion chromatography, high performance gel permeation chromatography and infrared chromatography. The protective effect and mechanism of CDPs on high glucose-induced injury in HK-2 cells were evaluated. Results: The weight-average molecular masses of CDPs were 8 031, 4 198, and 3 444 Da, which were primarily composed of glucose, galactose, rhamnose, mannose and arabinose, and may contain both α- and β-glycosidic bonds. CDPs reduced oxidative damage in HK-2 cells treated with high glucose and mitigated the impairment of mitochondrial membrane potential. The relative expression of Toll-like receptor 4 (TLR4), phosphorylated nuclear factor (NF)-κB p65, and phosphorylated inhibitor α of NF-κB (p-IκBα) in HK-2 cells significantly decreased after intervention with different concentrations of CDPs (P < 0.05). Conclusion: CDPs had the ability to reduce high glucose-induced renal tubular epithelial cell injury by inhibiting the TLR4/NF-κB signaling pathway to promote cell proliferation and inhibit oxidative stress and apoptosis.